Kualitas Pelaksanaan Online Public Relation Pemerintah Provinsi Bangka Belitung melalui babelprov.go.id ditinjau dari Penerapan Prinsip The 7C’s Framework - Achmad Riyadi; Iksander Salam (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
One of the effectiveness of babelprov.go.id is indicated by the high level of visits (high traffic) and how long visitors stay on the website (bounce rate). Therefore the role of the babelprov.go.id interface is significant in increasing the traffic as part of the online public relations activities in Bangka Belitung Province. As a part of the communication process, the design of babelprov.go.id is merely intended to support the success of the online public relations it carries. The study aimed to determine the degree of the online public relation implementation on babelprov.go.id reviewed from the 7 C's Framework models and to determine what the most dominant model of the 7C's Framework was that affected the quality of the babelporv.go.id. By using a descriptive-analytical with a qualitative approach, the research suggest that the implementation of online public relations through babelprov.go.id has been quite ideal because it has fulfilled five of the seven models required in the 7 C's Framework. As the second finding, the most dominant model of the 7C's Framework models that affects the quality of the site interface is the content model which focuses on more information posted on the web.